Respuesta :

Answer:

[tex]x + \frac{5}{3}-x - \frac{3}{2} = \frac{1}{6}[/tex]

Step-by-step explanation:

Given

[tex]x + \frac{5}{3}-x - \frac{3}{2}[/tex]

Required

Solve

[tex]x + \frac{5}{3}-x - \frac{3}{2}[/tex]

Collect like terms

[tex]x + \frac{5}{3}-x - \frac{3}{2} = x -x+ \frac{5}{3} - \frac{3}{2}[/tex]

[tex]x + \frac{5}{3}-x - \frac{3}{2} = \frac{5}{3} - \frac{3}{2}[/tex]

Take LCM

[tex]x + \frac{5}{3}-x - \frac{3}{2} = \frac{10 -9}{6}[/tex]

[tex]x + \frac{5}{3}-x - \frac{3}{2} = \frac{1}{6}[/tex]

ACCESS MORE
EDU ACCESS
Universidad de Mexico